2012
DOI: 10.1111/j.1365-2125.2012.04260.x
|View full text |Cite
|
Sign up to set email alerts
|

Population PK/PD analysis of metformin using the signal transduction model

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Metformin, a biguanide glucose lowering agent, is commonly used to manage type 2 diabetes.• The molecular mechanisms of metformin have not been fully identified, but turnover of biomarkers such as glucose and signalling pathways or translocation of glucose transporters are closely related to the glucose-lowering effects of metformin.• The PK/PD of metformin have been investigated in healthy humans and patients with type 2 diabetes mellitus and modelling has been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…Finding covariates to explain PK variability for a better metformin dosing has been a focus of metformin PK research for long, and clearance has previously been reported to be highly variable . However, in our study, the variability was only 16%.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Finding covariates to explain PK variability for a better metformin dosing has been a focus of metformin PK research for long, and clearance has previously been reported to be highly variable . However, in our study, the variability was only 16%.…”
Section: Discussioncontrasting
confidence: 59%
“…Several covariates have previously been reported to affect metformin PK. Considering that metformin is eliminated primarily through the kidneys, it is unsurprising that kidney function is predictive of metformin clearance in most metformin PK models . Due to this, we included kidney function in the structural model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A steady-state with respect to the composition of red blood cell MTX-PGs is only reached after several months, 34 often paralleling clinical improvement 35 . Although on a different time scale (hours and days), the distribution volume for metformin increases from about 1.6 L/kg after a single dose 36 to about 4 L/kg 25 under continuous dosing. This indicates a large tissue reservoir, mainly but not only dominated by expression and activity of the various transporters.…”
Section: Resultsmentioning
confidence: 98%
“…Several factors contribute to the individual variations in PK, including age, renal function, and genetic polymorphisms of metformin transporters . The variability in PK likely affects metformin pharmacological effects; a population PK/PD model has been established between metformin concentration and the glucose‐lowering effects of metformin . Recently, a single‐nucleotide polymorphism (SNP) near the ataxia telangiectasia mutated ( ATM ) gene was identified as accounting for a small fraction (2.5%) of the variance in metformin response…”
mentioning
confidence: 99%